Substitusi Tepung Ampas Tahu Pada Pengolahan Kue Bay Tat - Fesy Hendria Wati; Diah Azhari; Darius Darius; Ririn Afriani (Student Research Journal, 2024)
Tofu dregs flour is obtained from drying tofu dregs, which still have high protein and fiber content. It can be used as a substitute for wheat flour in processing a typical Bengkulu cake, namely bay tat cake. This research aims to analyze the effect of substitution of tofu dregs flour on the physical, chemical, and organoleptic properties of bay tat cake. This research method includes processing tofu dregs flour and processing bay tat cake with tofu dregs flour substitution treatment of 2.5%, 5%, 7.5%, 10%, 12.5%, and 15%. The analysis in this research includes yield, texture, water content, protein, fiber, carbohydrates, organoleptic (color, taste, aroma, texture), and analysis of the benefits of bay tat cake. The results of the analysis of the yield of bay tat cake with the substitution of tofu dregs flour were between 85.81% and 88.66%. The results of the texture analysis of the bay tat cake were between 8.69% and 19.23%. The results of the analysis of the water content of the bay tat cake were between 15.13% and 15.80%. The protein analysis results for bay tat cakes were between 14.07% and 16.46%. The results of the analysis of the highest carbohydrate content of bay tat cake were in the 15% tofu dregs flour substitution treatment, namely 47.00%. The results of the analysis of the fiber content of bay tat cake were between 1.12% to 1.53%. The results of the organoleptic analysis of the color of the bay tat cake were between 3.55 (somewhat like) to 4.5 (like). The organoleptic taste of bay tat cake is between 3.5 (somewhat like) to 4.4 (like). The results of the organoleptic analysis of the aroma of bay tat cake were 3.2 (somewhat like) to 4.35 (like). The texture analysis of the bay tat cake was between 3.15 (somewhat like) to 4.4 (like). Analysis of the profits of bay tat cake with 2.5% substitution of tofu dregs flour, namely Rp. 1,292/pack or Rp. 1,085.28 per month. Key Words: Bay Tat, Tofu Dregs Flour, Protein Content, Fiber Content, Substitution